E-Learning 3.0 Framework Adoption: Experts’ Views - Miranda, P.; Isaías, P.; Costa, C.; Pifano, S. (Lecture Notes in Computer Science, 2016)
The pervasiveness of the Semantic Web in educational contexts is acquiring a growing importance also at the level of e-Learning. The improvements it promises to introduce in online education are causing interest and curiosity in terms of its implementation and practical repercussions for learning. Since it is in its early stages it becomes important to explore the conditions that will favor its adoption. In order to delineate its prosperous deployment, this paper presents the outline of a Critical Success Factors framework. The purpose of this paper is to collect the point of view of e-Learning experts with regards to this framework. The experts were presented with the framework via semi-structured interviews and they were asked to review its core elements. The results of the data collection provide a substantial validation of the framework and reiterate its relevance in delimiting the proliferation of e-Learning 3.0.